Coagulated Rhythm [Review of Li, Li Fang and Hai Tao Yang. Coagulated Rhythm: the Theoretical Framework and Aesthetic Interpretation of Naxi Musical Iconography. Kunming: Yunnan People’s Press, 2002, iii+337]. - Paul Y. Cheung (Ilha do Desterro)
Heterogeneity is a recurrent theme and simultaneously a research focus of Cultural Studies. Not unrelated to this is the focus on complex diachronic and synchronic variability in language and discourse as demonstrated within the broad range of epistemologies in Linguistics and Sociolinguistics in particular. The ongoing debate concerning disciplinary boundaries of Cultural Studies and Sociolinguistics and related entities such as Anthropology, Gender Studies, Media Studies and Sociology is itself indicative of heterogeneity, complexity and variability. These themes emerge from the rich descriptive study offered through a kind of kaleidoscopic vision that is the monograph Coagulated Rhythm: the Theoretical Framework and Aesthetic Interpretation of Naxi Musical Iconography.